Phonemic fluency quantity and quality: Comparing patients with PSP, Parkinson's disease and focal frontal and subcortical lesions. (12th March 2021) - Foley, Jennifer A.; Niven, Elaine H.; Abrahams, Sharon; Cipolotti, Lisa
Abstract: Progressive supranuclear palsy (PSP) can be difficult to distinguish from Parkinson's disease (PD), but has a much graver prognosis. PSP is characterised severely reduced output on measures of phonemic fluency, suggesting that it may be a specific marker of PSP. However, reduced phonemic fluency has also been noted in PD, and very few studies have actually compared phonemic fluency in PSP and PD. Although anecdotal reports suggest that phonemic fluency output in PSP may have specific characteristics, with more low-frequency words and perseverative errors, no study to date has formally explored this. Further investigation into phonemic fluency output and its cognitive and neuroanatomical correlates is now critical for improving our understanding of the verbal fluency in PSP. In this study, we compared phonemic fluency characteristics (including quantity, frequency and error rates) in patients with PSP, PD and focal frontal or subcortical lesions, and age- and education-matched healthy controls. We then compared these characteristics with performance on extensive neuropsychological testing. We found that PSP patients generated significantly fewer words than patients with PD and patients with right frontal focal lesions, and healthy controls. Phonemic fluency was also significantly reduced in patients with left frontal and subcortical focal lesions. However, there were no significant group differences in word frequency or error rates. Phonemic fluency was best predicted by performance on the Vocabulary and Hayling neuropsychological tests. We argue that these findings provide important evidence that reduced phonemic fluency is a hallmark of PSP and argue that the specificity of this impairment betrays an underlying impairment in energization, reflecting dysfunction of left frontal and subcortical networks. Highlights: Reduced phonemic fluency is the neuropsychological hallmark of PSP. This reflects underlying impairment in energization. Phonemic fluency is subserved by left frontal and subcortical networks.